Activation of Nrf2 by ischemic preconditioning and sulforaphane in renal ischemia/reperfusion injury: a comparative experimental study - Shokeir, A A; Barakat, N; Hussein, A M; Awadalla, A; Harraz, A M; Khater, S; Hemmaid, K; Kamal, A I (Physiological research, 2015)
Objectives of the study were to investigate impact of ischemic preconditioning (Ipre) and sulforaphane (SFN) and combination of them on nuclear factor 2 erythroid related factor 2 (Nrf2) gene and its dependent genes, heme oxygenase-1 (HO1) and NADPH-quinone oxidoreductase1 (NQO-1) and inflammatory cytokines TNF-alpha, IL1beta, and intercellular adhesion molecule-1 (ICAM1) and caspase-3 in renal ischemia/reperfusion (I/R) injury. Ninety male Sprague Dawely rats were classified into 5 groups (each consists of 18 rats): sham, control, Ipre, sulforaphane and Sulfo+Ipre. Each group was subdivided into 3 subgroups each containing 6 rats according to time of harvesting kidney and taking blood samples; 24 h, 48 h, and 7 days subgroups. Renal functions including serum creatinine, BUN were measured at basal conditions and by the end of experiment. Expression of Nrf2, HO-1, NQO-1, TNF-alpha, IL-1beta, and ICAM-1 was measured by real time PCR in kidney tissues by the end of experiment. Also, immunohistochemical localization of caspase-3 and chemical assay of malondialdehyde (MDA), GSH and SOD activity were measured in kidney tissues. Both Ipre and SFN improved kidney functions, enhanced the expression of Nrf2, HO-1, and NQO-1, attenuated the expression of inflammatory (TNF-alpha, IL-1, and ICAM-1) and apoptotic (caspase-3) markers. However, the effect of sulforaphane was more powerful than Ipre. Also, a combination of them caused more improvement in antioxidant genes expression and more attenuation in inflammatory genes but not caspase-3 than each one did separately. Sulforaphane showed more powerful effect in renoprotection against I/R injury than Ipre as well as there might be a synergism between them at the molecular but not at the function level.
Keywords: Oxidative Stress; kombinovaná terapie; oxidační stres; sulfoxidy; isothiokyanatany; cytokiny; NF-E2-Related Factor 2; Acute Kidney Injury; krysa rodu Rattus; výsledek terapie; zvířata; Sulfoxides; potkani Sprague-Dawley; Male; Isothiocyanates; Treatment Outcome; Cytokines; Reperfusion Injury; faktor 2 související s NF-E2; Rats; přivykání k ischémii; Rats, Sprague-Dawley; Animals; Combined Modality Therapy; mužské pohlaví; akutní poškození ledvin; Ischemic Preconditioning; reperfuzní poškození